2021
DOI: 10.3390/ijms22115736
|View full text |Cite
|
Sign up to set email alerts
|

Hijacked Immune Cells in the Tumor Microenvironment: Molecular Mechanisms of Immunosuppression and Cues to Improve T Cell-Based Immunotherapy of Solid Tumors

Abstract: The understanding of the tumor microenvironment (TME) has been expanding in recent years in the context of interactions among different cell types, through direct cell–cell communication as well as through soluble factors. It has become evident that the development of a successful antitumor response depends on several TME factors. In this context, the number, type, and subsets of immune cells, as well as the functionality, memory, and exhaustion state of leukocytes are key factors of the TME. Both the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 248 publications
1
41
0
Order By: Relevance
“…DCs and T cells are both suppressed by IL-10. Meanwhile, IFN-γ, TNF-α, IL-2, and IL-1β play crucial parts in killing tumor cells according to previous researches (West et al, 2013;Garris et al, 2018;Balta et al, 2021). Furthermore, another study showed that intratumoral DC's IL-12 cytokine signaling leads to anti-tumor immunity, and the antitumor cytokines IFN-γ and IL-12 are stimulated by immunotherapy.…”
Section: The Effects Of Astragalus Polysaccharide On Immune Cell Constituents Of Tumor Microenvironmentmentioning
confidence: 94%
“…DCs and T cells are both suppressed by IL-10. Meanwhile, IFN-γ, TNF-α, IL-2, and IL-1β play crucial parts in killing tumor cells according to previous researches (West et al, 2013;Garris et al, 2018;Balta et al, 2021). Furthermore, another study showed that intratumoral DC's IL-12 cytokine signaling leads to anti-tumor immunity, and the antitumor cytokines IFN-γ and IL-12 are stimulated by immunotherapy.…”
Section: The Effects Of Astragalus Polysaccharide On Immune Cell Constituents Of Tumor Microenvironmentmentioning
confidence: 94%
“…Finally, another molecule that is significantly involved in the generation of a pro-tumor setting is the vascular endothelial growth factor (VEGF), highly secreted by tumor cells and by pro-tumoral TAMs [ 127 , 128 , 129 , 130 ].…”
Section: Mechanisms Allowing Cancer Immune Evasion a Lesson From 2d C...mentioning
confidence: 99%
“…In many tumors, like colorectal cancer, breast cancer, ovarian cancer or bladder cancer, the infiltration of CD8 + CTLs is thought to be a good prognostic marker [46]. However, in large, progressed tumors, CTLs are often exhausted and dysfunctional and express high levels of exhaustion markers like PD-1, lymphocyte-activation gene 3 (LAG-3), cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) or TIGIT [47].…”
Section: Tumor-infiltrating Lymphocytes (Tils)mentioning
confidence: 99%
“…In most tumors, the presence of M2 macrophages correlates with a poor prognosis. It is now clear that the classification of TAMs into M1 and M2 macrophages is too crude, as TAMs exist in several subtypes with very high plasticity [47].…”
Section: Myeloid Cellsmentioning
confidence: 99%